Capitalization as a Tool for Managing the Development of Industry and Rail Transport - Posokhov, Igor Mikhailovich; Cherepanova, V. O.; Podrez, Olha (My University, 2019)
The Ukrainian real economy encounters similar problems that do not allow its rapid development – high level of wear of productive assets, lack of modern equipment, outdated technologies, inappropriate environmental measures, high rate of occupational injury, etc. All this requires designing of new tools to manage the development of such important sectors of economy as industry and rail transport. Therefore, the urgent issues at the current stage of development of these industries include the definition of conditions for fixed assets capitalization and the sources of its financing. The scientific novelty of the results is identification and justification of the capitalization main components, determining the sources of funding and the mechanism for their attraction. The tool for managing the productive and environmental protection assets capitalization has been designed which is optimized using a twodimensional dynamic programming model. The results obtained are the basis for the practical solution of the problem, and for further scientific research. This approach allows solving the problem of rail transport and industrial enterprises capitalization in a comprehensive manner, which contributes to their sustainable development.